Рассказы - Хемингуэй Эрнест (Школа классики, 1998)
10-11 кл. Экземпляры: Селтинская районная библиотека (аб) (20190423) / Инвентарный номер: 181205 / Цена: 16.39 / Авт.знак: Х 37 / ГРНТИ: 17.82 / ББК: 84(7Сое)